An Annotated Translation of Hasting and Meyer’s No Rules Rules: Netflix and Culture of Reinvention From English into Indonesian - Hilmi Mahdi Mahardika (Jurnal Linguistik Terapan, 2025)
This research focuses on annotated translation, which involves translating with commentaries. The study examines No Rules Rules: Netflix And Culture of Reinvention (2020), specifically Chapters 1 and 2, using Newmark and Chesterman's translation theories. The researcher identified translation challenges and provided solutions through introspective and retrospective methods. Three main problem categories were found: understanding (16 cases), transfer (9 cases), and a combination of both (15 cases), totaling 40 annotated items.  To overcome these difficulties, the researcher applied various translation strategies, including literal translation, synonymy, cultural filtering, free translation, idiomatic translation, loan/calque, paraphrase, cultural equivalence, functional equivalence, and contextual equivalence. Multiple online dictionaries (Merriam Webster, Oxford, Longman, Cambridge, Britannica, Urban Dictionary, and Collins), relevant websites, and previous studies were also used to support the translation analysis. Keywords: translation, annotated translation, business book, strategies